A sediment record of terrestrial organic matter inputs to Dongting Lake and its environmental significance from 1855 to 2019. (November 2021) - Wang, Yanhua; Huang, Yu; Tian, Jiaming; Li, Chunhua; Yu, Kangkang; Zhang, Mingli; Lang, Xiulu; Sun, Tian
Highlights: The sediment deposition rate increased between 0.03 and 2 g cm −2 a −1 during 1855–2019. Strong dominance of odd-numbered n -alkanes maximized at C15, C27, C29, and C31 . Main source of buried OC changed from C3 plants to algae since Anthropocene. Three Gorges and agricultural activities affected trends of OC burial changes. Abstract: The extensive anthropogenic activities and their potential impacts on lakes during the Anthropocene could be recorded in the sediments. In this study, the composition of biomarkers (i.e., n -alkanes and n -fatty acids), total organic carbon (TOC), and particle size in 210 Pb-dated sediment cores from West Dongting Lake were investigated to trace the historical trend of anthropogenic inputs and their environmental significance. The TOC content was in the range of 3.15–27.32 mg g −1 . The n -alkanes and n -fatty acids were distributed from C11 –C33 and C12:0 –C34:0, respectively. The short- and long-chain biomarkers accounted for a significant proportion of the total. Aquatic plants and algae living in West Dongting Lake were the main source (short-chain) followed by leaf waxes derived from terrestrial C3 plants (long-chain), as demonstrated by their concentrations. The variations of the key indicators i.e., the carbon preference index (CPI), aquatic plant n -alkane proxy ( P aq ), vascular plant n -alkane proxy ( P wax ), and the ratio of unit short- to long-chain n -alkanes (L/H) also indicated that the aliphatic hydrocarbon fractions were mainly composed of short- and long-chain biomarkers. The sedimentary biomarkers had a significant temporal heterogeneity, which was controlled by different factors and sedimentary processes. Fine particles (<16 µm) were the dominant particle size (66.91%–78.52%) in the sediment. Both values of the dry/wet climate proxy (Kd ) and average particle size were consistent over time. The dominance of terrestrial C3 plant-derived long-chain molecules gradually changed, with algae-derived short-chain molecules then becoming dominant. The hot and drought climate conditions and enhanced agricultural inputs from 1855 to 2019 in the watershed resulted in a decrease of terrestrial C3 plants and rapid growth of algae in the lake water.